Interactive effect of harvesting seasons and drying methods on the quality of jatropha zeyheri tea leaves - Ngoetjana, Makgabiso Constance (My University, 2023)
Worldwide, second to water, tea is in the upper class of the most consumed beverages and has greater popularity. The increased consumption and popularity of tea is associated with its health promoting properties and medicinal use. Jatropha zeyheri is being used for various purposes due to its nutritional and medicinal properties. In some parts of South Africa, the leaves of J. zeyheri are harvested during winter when the leaves are dry to make tea beverage. However, appropriate harvesting seasons and suitable drying methods that will contribute towards optimising the quality of J. zeyheri tea leaves is not documented. Therefore, the objectives of this study were two folds, namely, (i) determine whether harvesting seasons and drying methods have an effect on phytochemicals and antioxidants activity of J. zeyheri leaves and (ii) investigate whether harvesting seasons and drying methods have an effect on essential and non-essential mineral elements of J. zeyheri leaves. Leaves of J. zeyheri were collected from Khureng village, Lepelle-Nkumpi Municipality, Limpopo Province, South Africa. To achieve the objectives, a 3 x 4 factorial experiments, with first factor comprising harvesting seasons (autumn, winter and summer), while the second factor constituted the drying methods (shade, sun, oven and freeze drying), were arranged in a randomised complete block design (RCBD), with 9 replications. Approximately, 1 g of ground powdered plant materials were extracted with 10 mL of acetone. After the preparations, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay was used to quantify the antioxidant activity (AA) of the acetone extracts of plants. The total phenol content (TPC) and total tannin content (TTC) in each plant extract were determined using the Folin-Ciocalteu assay method. The total flavonoid content (TFC) was determined using the Aluminium Chloride colorimetric assay. The absorbance for AA and phytochemicals were achieved using UV/visible spectrophotometer. Mineral elements were determined using Inductively Coupled Plasma Emission Spectrometer-9000. Harvesting seasons had highly significant (P ≤ 0.01) effects on TPC, TFC, TTC and AA contributing 68, 86, 80 and 65% in TTV, respectively. Drying methods had highly significant effects on TPC, TFC, and AA contributing 18, 10 and 18% in TTV, respectively, whereas drying methods had no significant (P ≤ 0.05) effect on TTC. Interaction of drying methods and harvesting seasons had highly significant effects on TPC and AA, contributing 10 and 14% in TTV, respectively, whereas total TFC was significantly affected, contributing 2% in TTV. However, TTC was not affected by the interaction between harvesting seasons and drying methods. Summer harvesting season was more efficient in retaining the highest TPC and AA, autumn harvesting season retained the highest TFC while, winter retained TTC. Drying methods demonstrated that oven drying is more efficient in retaining TPC and TFC of J. zeyheri tea leaves, as compared to other drying methods. However, freeze drying is more effective in retaining AA of J. zeyheri tea leaves. Interactively, the results of this study conclude that summer and oven drying had the highest TPC and TFC, however summer and freeze drying had the highest AA. Harvesting seasons had highly significant effect on essential mineral elements, Ca, Cu, Fe, K, Mn, Ni, and P contributing 14, 50, 25, 42, 53, 74 and 49% in TTV, respectively, whereas Zn was significantly affected, contributing 13% in TTV. However, harvesting seasons had no significant effect on Mg. Drying methods had highly significant effects on Ca, Fe, Mg, Mn and P contributing 57, 37, 57, 25 and 19% in TTV, respectively, whereas, Cu and K were significantly affected, contributing 14 and 13% in TTTV. However, no significant effect was observed on Ni and Zn. Interaction of harvesting seasons and drying methods had highly significant effects on Ca, Cu, Fe, K, Mn, P and Zn contributing 25, 26, 30, 32, 20, 24 and 48% in TTV, respectively, whereas Mg was significantly affected contributing 14% in TTV. However, no significant effect was observed on Ni. Summer harvesting season accounted for the highest content of essential mineral elements (Fe, Ni, P and Zn), additionally summer harvesting accounted for the highest non-essential mineral elements (Al and Na). Drying methods demonstrated that sun and oven drying accounted for the lowest contents of the selected elements, whereas most of the elements were retained by freeze and shade drying. Interactively summer and shade drying retained most of the mineral elements. In conclusion, the results of this study suggest that harvesting of J. zeyheri tea leaves should be done during the summer season and subjected to oven-drying for improved accumulation of phytochemicals. However, for improved accumulation of AA harvested leaves should be freeze-dried, whereas, for improved accumulation of mineral elements, the leaves of J. zeyheri should be subjected to shade and freeze-drying methods.
Thesis (M.Sc. (Horticulture)) -- University of Limpopo, 2023
Keywords: Jatropha curcas; Nutmeg tree; Jatropha; Tea; Tea -- Harvesting